Assessment of Phenotypic and Reproductive Characteristics of Local Donkeys in Marathwada Region (Indian Journal of Animal Production and Management, 2024)
A total of 1007 local donkeys were selected  for the study of phenotypic and reproductive  characters of local donkeys from different districts  of the Marathwada region in Maharashtra state.  Statistically non-significant differences were found  in most of the phenotypic parameters. Four different  body coat colour patterns i.e., grey, brown, white,  and dark red brown were observed with percentage  as 48.46, 21.54, 25.12 and 4.86%, respectively.  Most of donkeys (96.02 %) were black muzzled with  convex forehead (93.24%), white marking above  muzzle (66.53%), white marking above eyes  (67.72%), white marking posterior to the mandible  (70.30%), dark brown lining around extremity of ear  pinna (88.97 %), long white hairs at inner side of ear  pinna (100%) and bearing dark strip starting from  poll to switch of tail and forming cross with another  dark strip at shoulder (73.48%). The mean age at  puberty, age at first service, age at first oestrus,  oestrus cycle duration, oestrus duration, age at first  covering, age at first conception, no. of  services/conception, age at first foaling, service  period, foaling interval, gestation period, lifetime no.  of foaling of adult female local donkeys in  Marathwada region were 2.70±0.02 years,  2.79±0.02 years, 2.77±0.03 years, 6.86±0.084  days, 23.80±0.55 days, 2.96±0.01 years, 5.9±0.07  years, 1.82±0.06, 4.44± 0.01 years., 1.14±0.01  years, 2.25±0.01 years, 340.8±0.27 days and  5.98±0.07, respectively.
Keywords: local donkeys; Marathwada; Maharashtra; phenotypic characters; reproductive characters